Підходи до опрацювання загальної лексики зі студентами немовних факультетів - Скиба, Оксана Миколаївна (Видавничий дім «Гельветика»; ПУ «Причорноморський науково-дослідний інститут економіки та інновацій», 2024)
Робота з лексичним матеріалом є дуже важливою під час роботи зі студентами немовних спеціальностей, адже спілкування на загальні теми є невіддільною частиною та є ціка вими для студентів, дозволяють розвивати усне та письмове мовлення здобувачів освіти. Під час добору вправ та видів діяльності на опрацювання та запам’ятовування лексики необхідно враховувати типи пам’яті, які залучені до цього.
Approaches to general vocabulary processing with students of non-linguistic schools
The article is devoted to highlighting approaches to the study of general vocabulary with students of non-linguistic schools. Despite the fact that special attention is paid to the study of a foreign language for professional purposes during the teaching of English, it is necessary to pay attention to the study of general vocabulary, which increases the motivation and interest of students in studying the subject. It is established that working with vocabulary is a complex and long-term process, during which it is necessary to take into account the goals of learning, the correspondence of lexical units to the level of students’ knowledge, and to ensure multiple repetition of lexical units in the learning process. When working on lexical material with students, it is necessary to understand the peculiarities of the functioning of short-term (retaining and memorizing a significant amount of information, but only for a short period of time), working (longer work with lexical units), and longterm types of memory. In order for words to enter long-term memory, it is necessary to repeat the lexical units many times; use the same lexical unit in different contexts; dose the study of new units in small portions; control and self-control the study of lexical units; take into account the cognitive depth of lexical units; and visualize the lexical units being studied. It is found that to achieve positive results, it is necessary to divide the vocabulary into separate parts. It is recommended to work with lexical units at the level of words and phrases, automate students’ actions during completing exercises or texts with active lexical units, and stimulate students to independently use lexical units during written or oral speech. Approaches to working with general vocabulary are illustrated on the topic «Travelling».
Keywords: general vocabulary, students of non linguistic schools, English; лексика загального вжитку, студенти немовних факультетів, англій ська мова.